Teaching material development oriented on the saintific approach of 5M in learning automotive basic technology - Supriadi, Supriadi; Suparno, Suparno; Giatman, M.; Edidas, Edidas (Jurnal Pendidikan Teknologi Kejuruan, 2020)
The purpose of this research is to develop interactive learning media on computer and basic networks subject that are valid, practical and effective. This reasearch is used the Four-D design model that is applied to develop and test the validity, practicality and effectiveness of interactive learning media in computer and basic networking learning. The research is used the Four-D model include defining, designing, developing, and distributing. The results of the validity test on interactive learning media are valid. Based on teachers and students responses about instructional media shows the results of interactive learning media are very practical and learning outcomes from students indicate the learning media has been effectively used for computer and basic networking learning. The analysis resultshows that interactive learning media is better in improving student learning processes